2016
DOI: 10.1159/000442041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Insertion Techniques of a Cochlear Implant Electrode on the Intracochlear Pressure

Abstract: To achieve a functional atraumatic insertion, low intracochlear pressure changes during the procedure are assumed to be important. The aim of this study was to observe intracochlear pressure changes due to different insertion techniques in a cochlear model. Cochlear implant electrode insertions were performed in an artificial cochlear model to record intracochlear pressure changes with a micropressure sensor to evaluate the maximum amplitude and frequency of pressure changes under different insertional conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 13 publications
0
37
2
Order By: Relevance
“…Although the measured conditions were artificial, using a model, clinical relevance is highly probable since the measured values are, in comparison with other studies [35, 8, 9], by far the highest. Importantly, our mean maximum pressure amplitude values of 933.6 PA up to 1598 PA are above the measured pathologically relevant level in the guinea pig of +700 PA [17].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although the measured conditions were artificial, using a model, clinical relevance is highly probable since the measured values are, in comparison with other studies [35, 8, 9], by far the highest. Importantly, our mean maximum pressure amplitude values of 933.6 PA up to 1598 PA are above the measured pathologically relevant level in the guinea pig of +700 PA [17].…”
Section: Discussionmentioning
confidence: 89%
“…The development of atraumatic opening of the round window has led to the development of specific opening tools [6]. Insertional factors have been observed experimentally under force aspects [7] and even under the point of pressure occurrence in terms of speed [8], moisturized insertions [4], and tremor aspects [9]. Different studies have shown the clinical relevance of these findings [1012].…”
Section: Introductionmentioning
confidence: 99%
“…These studies investigated the effects of insertion speed (18), insertion technique (i.e. unsupported, supported, or automated) (19), and size of the opening in the round window (32), each revealing generation of large static pressures (~ 200 Pa, or 140 dB SPL) during the insertion. It is interesting that no transient pressures are reported; however this may be due to the use of a plastic model, compared to cadaveric temporal bones in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent papers reported intracochlear pressure changes for several speeds of electrode insertions (via a linear actuator) (18), and different insertion techniques (19) in an artificial cochlear model. Mean maximal intracochlear pressures were reported up to 170 Pa, or ~140 dB SPL peak; however, no large transients were observed, possibly because these studies were conducted in an artificial cochlea model.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of intraoperative trauma to the cochlea during hearing preservation implantation is well established, and several mechanical factors, such as insertional force, underwater insertion, the presence of blood or bone dust, and electrode specifications, have been identified as being of significance [Roland, 2005;Bas et al, 2012;Rajan et al, 2013;Anagiotos et al, 2016;Todt et al, 2016a;Eshraghi et al, 2017] [Basta et al, 2007;Mittmann et al, 2014Mittmann et al, , 2016Mittmann et al, , 2017Mittmann et al, , 2018Todt et al, 2014aTodt et al, , b, 2016aTodt et al, , b, 2017a.…”
Section: Discussionmentioning
confidence: 99%